Influence of Alkaline ratios on strength properties of Fly ash-Ground Granulated Blast Furnace Slag Based Geopolymer Mortars. Issue 1 (December 2020) - Venu, M.; Rao, G. Mallikarjuna; Kumar, Y. Anil; Madduru, Sri Rama Chand; Bellum, Ramamohana Reddy
Abstract: Geopolymer concrete is a new and alternative to cement concrete, thus decreasing greenhouse emissions and leading to better construction practices. This can be produced by complete replacement of cement with pozzolanic materials such as Fly Ash (FA), Ground Granulated Blast Furnace Slag (GGBS) and activation through alkaline activator solution. The present study aims to investigate the effect of 8M sodium hydroxide solution for the chemical ratios of Na2 SiO3 to NaOH are 1.5, 2.0, 2.5, and 3 with different combinations of fly ash and GGBS. The cast specimens were outdoor cured and tested at the age of 1, 3, 7, and 28 days for compressive strength, followed by XRD analysis to identify the mineralogical variations with a change in parameters. The obtained results concluded that GGBS content with 8M concentration of sodium hydroxide in the mix increases the compressive strength of geopolymer mortar. The optimum dosage of Na2 SiO3 /NaOH was 2.5 based on the compressive strength of mortar. The compounds responsible for strength were identified through XRD analysis as N-A-S-H gel and C-A-S-H gel in mixes with fly ash and GGBS as binders.